Respostas

2014-06-26T17:57:30-03:00
Com A=-x³+5x² 
B=-2+2x²-10x e C=6x³-6x+30 determine o resultado da divisao de A+B+C por x²-2x+6

A = x
⁵ - x³ + 5x²
B = - 2x⁴ + 2x² - 10x
C = 6x³ - 6x + 30

A + B + C divide por x² - 2x + 6

x
⁵ - x³ + 5x² -2x⁴ + 2x² - 10x + 6x³ - 6x + 30  ---------- arrumar a casa
x⁵ - 2x⁴ -x³ + 6x³ + 5x² + 2x² - 6x - 10x + 30

x⁵ - 2x⁴     + 5x³   +     7x²    -16x   + 30 divide por x² - 2x + 6

 



          x⁵ - 2x⁴ + 5x³ + 7x² - 16x +30        |___x² - 2x + 6______ 
       -  x⁵ +2x⁴  -6x³                                   x³  - x  +  5
       ------------------
           0    0    -  x³ + 7x² - 16x
                       + x³  - 2x² + 6x
                         ------------------
                          0     5x² - 10x   + 30
                              - 5x² + 10x   - 30
                         ----------------------------
                                0         0      0

x⁵ - 2x⁴ + 5x³ + 7x² - 16x +30  : x² - 2x + 6 =  x³  - x  +  5

Resposta = x³ - x + 5
     
1 5 1